A new species of Parotocinclus with reduced adipose fin (Loricariidae: Hypoptopomatinae), from the rio Jacuípe basin, Bahia State, Brazil - Silva-Junior,Dario Ernesto da (2020)
ABSTRACT A new species of Parotocinclus, apparently endemic to the rio Jacuípe basin, Bahia State, Brazil, is described. The new species is distinguished from congeners, except P. bidentatus, P. cabessadecuia, P. dani, P. halbothi, P. muriaensis, P. pentakelis, P. seridoensis, and P. spilurus, by the presence of a reduced adipose fin. The new species differs from the aforementioned species by the absence of unicuspid accessory teeth, abdomen with broad naked areas between lateral and medial patches of plates, and snout tip completely covered by plates and odontodes. The adipose fin of the new species is restrict solely to the adipose-fin spine, lacking the adipose-fin membrane, a reduction pattern previously described to P. halbothi, a congener from rivers of the Amazonas and Marowijne basins.